Pembangunan Sistem Aplikasi Pemesanan Dan Penghantaran Burger Berasaskan Android - Ngasiman, Nur Siddiqah Husna; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2022)
The Android -Based Burger Ordering and Delivery Application is a burger ordering and delivery system for a small burger stall that sells various types of burgers. This ordering and delivery application was developed to make it easier for customers to order and purchase burgers and assist stall owners or admins in managing products and orders placed by customers. The development of this system is based on a prototype model. The activities in this prototype model identify problem statements and system objectives, identify system requirements, and design system interfaces and databases. The system was developed using Android Studio for admin development, and the client used Firebase as a database. This ordering and delivery application is designed to help from the aspect of ordering and purchasing burgers. It can benefit from the part of product management and orders that have been made by customers from the beginning of the process to completion to be more organized and efficient.